Pengaruh Model Project Based Learning dan Gaya Berpikir terhadap Kemampuan Memecahkan Masalah Mahasiswa Geografi - Alif Reza Nurhadi; Sugeng Utaya; Budi Handoyo (Graduate School of Universitas Negeri Malang, 2018)
Abstract: The purpose of this research is to determine the affect of project based learning model and thinking style on the problem solve abillity of geography students in the environmental geography course. This research method is quasi experimental with pretest-posttest 2x2 factorial design type. The subjects of this study were the geographic students of H-class as the experimental class and the G-class as the control class in the class of 2016. The analysis showed that there was an increase of students ability in solving the problem. The result of analysis shows that there is no influence of divergent and convergent thinking style to problem solving ability. The result of analysis shows that there is no interaction of learning model and thinking style to students problem solving ability. Abstrak: Tujuan penelitian ini adalah mengetahui pengaruh model project based learning dan gaya berpikir terhadap kemampuan memecahkan masalah mahasiswa geografi pada mata kuliah geografi lingkungan. Metode penelitian ini adalah quasi experimental dengan jenis pretest-posttest 2x2 factorial design. Subjek penelitian ini adalah mahasiswa geografi offering H sebagai kelas eksperimen dan offering G sebagai kelas kontrol pada angkatan 2016. Hasil analisis menunjukkan ada perbedaan peningkatan kemampuan mahasiswa dalam memecahkan masalah. Hasil analisis menunjukkan tidak ada pengaruh gaya berpikir divergen dan konvergen terhadap kemampuan memecahkan masalah. Hasil analisis menunjukkan tidak ada interaksi model pembelajaran dan gaya berpikir terhadap kemampuan memecahkan masalah mahasiswa.